2021
DOI: 10.1038/s41598-021-85236-z
|View full text |Cite|
|
Sign up to set email alerts
|

The impact of socioeconomic and stimulus inequality on human brain physiology

Abstract: The brain undergoes profound structural and dynamical alteration in response to its stimulus environment. In animal studies, enriched stimulus environments result in numerous structural and dynamical changes along with cognitive enhancements. In human society factors such as education, travel, cell phones and motorized transport dramatically expand the rate and complexity of stimulus experience but diverge in access based on income. Correspondingly, poverty is associated with significant structural and dynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Our demonstration of the computation and properties of this metric utilize EEG recordings obtained from 50 adults between the ages of 21 and 50 as previously described in [1]. EEG recordings were obtained while participants were sitting quietly for three minutes with their eyes closed (EC) or with their eyes open and looking at images on a laptop screen (EO).…”
Section: Methodsmentioning
confidence: 99%
“…Our demonstration of the computation and properties of this metric utilize EEG recordings obtained from 50 adults between the ages of 21 and 50 as previously described in [1]. EEG recordings were obtained while participants were sitting quietly for three minutes with their eyes closed (EC) or with their eyes open and looking at images on a laptop screen (EO).…”
Section: Methodsmentioning
confidence: 99%
“…Our demonstration of the computation and properties of this metric utilizes EEG recordings obtained from adults between the ages of 21 and 50, as previously described in [19]. EEG recordings were obtained from 50 participants sitting quietly for three minutes with their eyes closed (EC) or with their eyes open and looking at images on a laptop screen (EO).…”
Section: Human Eeg Recordingsmentioning
confidence: 99%
“…Historically though, most EEG research has been conducted in highly controlled settings of laboratories based in high-income settings, with little ethnic diversity amongst study participants ( Bhavnani et al, 2021 ). Given emerging evidence that some EEG metrics might be sensitive to cultural and contextual differences across global settings ( Knyazev et al, 2012 ; Alahmadi et al, 2016 ; Parameshwaran et al, 2021 ), it is critical to diversify the population of participants from whom inferences on brain development and function are drawn and ensure that low and middle income countries (LAMIC), in which the majority of the world’s population resides, are well represented in this important field of research ( Valdes-Sosa et al, 2021 ). Furthermore, these populations are the most likely to benefit from such research, since they reside in countries with a high prevalence of risk factors that adversely impact the developing brain and have the highest number of children with neurodevelopmental disorders ( Lu et al, 2016 ; Bitta et al, 2017 ), making it imperative to test the generalizability of the evidence that has accumulated from research in high-income settings.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence is beginning to accumulate on the feasibility and validity of using portable EEG devices in research studies ( Ekandem et al, 2012 ; Badcock et al, 2013 ; De Vos and Debener, 2014 ; Lau-Zhu et al, 2019 ). Most of this data has emerged from studies conducted on adult participants, including studies from our group which have demonstrated the utility of the EPOC device to collect data from adults in remote rural settings in India ( Parameshwaran et al, 2021 ). However, to our knowledge, there are no published reports demonstrating the utility of the EMOTIV EPOC device to collect EEG data on a large population-based sample of preschool children in low resource settings.…”
Section: Introductionmentioning
confidence: 99%